α-Glucosidase Inhibitory Activity of Fermented Okara Broth Started with the Strain Bacillus amyloliquefaciens SY07 - Yifang Gao; Wenhui Bian; Yuanyuan Fang; Peng Du; Xueting Liu; Xueru Zhao; Fengjuan Li (Molecules, 2022)
In this work, a new strain of Bacillus amyloliquefaciens SY07 isolated from a traditional fermented soybean food was reported to possess remarkable α-glucosidase inhibitor-producing ability. Different culture media were applied for the proliferation of B. amyloliquefaciens SY07, and it was found that fermented okara broth presented the highest α-glucosidase inhibitory activity, while Luria-Bertani medium showed a negative effect. The extract from fermented okara broth acted in a dose-dependent manner to inhibit α-glucosidase activity, with an IC50 value of 0.454 mg/mL, and main inhibitors in the fermentation extract presented a reversible, uncompetitive pattern according to Lineweaver–Burk plots. Moreover, 1-deoxynojirimycin, a recognized α-glucosidase inhibitor, was found in the extract. Results indicated that B. amyloliquefaciens SY07 could utilize okara, a by-product from the soy processing industry, to generate α-glucosidase inhibitors effectively, and be regarded as a novel excellent microbial candidate for safe, economical production of potential functional foods or ingredients with hypoglycemic effect.